Aspek Reproduksi Ikan Gabus (Channa sriata) di Rawa Banjiran Aliran Sungai Sebangau, Palangkaraya - Elen Selviana; Ridwan Affandi; Mukhlis Kamal (Institut Pertanian Bogor, 2020)
Snakehead fish (Channa striata) is one of fish species that lives in the flooding swamp area. The flooding swamp area is a shallow waters located in swampy forest area, has water temperature of 28-32°C, pH 3-4, and low oxygen content (2-4 mg/L). This study aimed to examine the pattern of reproduction in snakehead (Channa striata) in the area of flood swamp water. This study was conducted for 6 months from August 2016-January 2017. Samplings of fish were taken from upstream, middle, and downstream of Sebangau river in Central Borneo. Measurements of total length and body weight were carried out on 545 samples of the fish. The results of the research showed that the length growth of the fish was not as fast as the weight growth, the sex ratio of fish in gonads mature was 0.6:1.0 (male:female). The size of body length at the first gonad maturity in female snakehead was 27.75 cm and the male fish was 32.17 cm. The spawning season of snakehead fish took place from August to October and peak in October. Spawning of experimental fish was located in the downstream (station 3). Snakehead fish is a total spawner. Snakehead fish has a large reproductive potential with fecundity ranging from 55341 to 65507 eggs. Keywords: floodplain area, reproductive biology, snakehead